Increasing the Technological Efficiency of Well Killing Using Innovative Technologies - R. A. Gasumov; E. R. Gasumov; Yu. S. Minchenko; V. G. Kopchenkov; V. V. Fedorenko (Наука. Инновации. Технологии)
Introduction. The article considers the issue of assessing the technological efficiency of the well killing process, taking into account changes in the reservoir properties of the productive formation when using various compositions of process fluids. Innovative technologies are presented that are used when killing wells in various mining and geological conditions to block the bottomhole formation zone.Materials and methods of research. The study is based on a summary of many years of experience in the field of creation and practical use of process fluids for killing wells and on the results of theoretical, laboratory, bench studies of killing fluids and blocking compositions, performed in specialized scientific laboratories using specialized laboratory equipment according to standard methods for the oil and gas industry.Research results and discussion. The compositions of process fluids are presented, which are easily removed when inducing inflow from the formation, and which allow to provide the required pressure at the bottomhole, as well as to maintain the reservoir properties of the productive formation and prevent its damage. The results of killing wells with the use of various compositions of process fluids with high stability, low filtration, in a wide range of adjustable density and rheological properties, which allow creating the necessary repression on the formation and performing various operations in the well, are considered. The article also provides information on the analytical studies carried out within the framework of the given problem. The results made it possible to draw conclusions regarding the use of various types of fluids for killing oil, gas, gas condensate wells under conditions of abnormally low reservoir pressures and elevated reservoir temperatures. Consideration is given to the liquids with an acidsoluble condensable solid phase, the formation of which in solution is due to the occurrence of physicochemical processes between its components; biopolymer-based liquids containing various fillers and functional additives; viscoelastic compositions reinforced with solid-state lamellar and fibrous particles of organic and mineral origin (for example, bridging additive brand «OM-2C») based on commercially available polymer reagent «Binar»; emulsion-type kill fluids containing surfactants and a hydrocarbon phase. The main rheological and technological parameters, as well as the properties of the proposed process fluids for killing wells, are described.Сonclusions. Based on the study, it was determined that the most promising technology for killing wells under conditions of abnormally low formation pressures is the technology of preliminary blocking of the bottomhole formation zone using special compositions of process fluids with controlled rheological parameters, taking into account the characteristics of the formation, technologically applicable in special climatic conditions with low negative temperatures. It has also been established that ensuring high efficiency of repair work is impossible without performing theoretical calculations and laboratory studies with modeling the process of blocking the bottomhole zone during well killing and subsequent development.